Intracytoplasmic Crystalline Inclusions in the Hepatocytes of an Antelope - Sanjeev Gumber; Eric Lombardini; Bruce Williams; Nobuko Wakamatsu (Veterinary Medicine International)
This case report describes intracytoplasmic crystalline inclusions in the hepatocytes of a 13-year-old female Thomson's gazelle. Histologically, multifocal to coalescing areas of many hepatocytes contained large cytoplasmic vacuoles filled with pale eosinophilic homogeneous material and rare fine basophilic granules. Von Kossa staining showed the presence of calcium within cytoplasm, mainly in the inclusions, of hepatocytes. Transmission electron microscopy, scanning electron microscopy, energy dispersive X-rays analyses, and infrared spectroscopy on the liver showed the hepatocellular material consistent with protein and carbohydrate with secondary accumulation of calcium and phosphorus. It was concluded that crystalline inclusions may have been derived due to failure of normal physiological hepatocellular clearance associated with a severe chronic disease. To the authors' knowledge this is the first reported case of hepatocellular crystalline inclusions in an antelope.